The complete chloroplast genome of Scutellaria scordifolia (Labiatae) - Li, Junyi (Mitochondrial DNA B Resour, 2021)
Scutellaria scordifolia Fisch. ex Schrank Li is a traditional Chinese medicinal plant of genus Scutellaria from the Labiatae family. The complete chloroplast genome of was 152,336 bp in length, which contained 133 complete genes including 87 protein-coding genes (87 PCGs), 8 ribosomal RNA genes (8 rRNAs), and 37 transfer RNA genes (37 tRNAs). The GC content of chloroplast DNA was 38.3%. The corresponding values of the LSC, SSC, and IR regions were 36.3%, 32.5%, and 43.6%, respectively. Phylogenetic tree showed that the species from genus Scutellaria were divided into two monophyletic clades, and the divergence time of S. scordifolia was earlier than that of the other species.